Memories and Places of Disappearance: Public Statements by ESMA Perpetrators in Argentina (Tempo e Argumento, 2021)
The Escuela de Mecánica de la Armada (ESMA) was among the most active/busiest clandestine detention centers of the last military dictatorship (1976-1983). Through a complex process of remembrance, it has become an emblem of the most atrocious repression. This memory process involved “layers” of meaning that evolved on the basis of actions, narratives and debates of different actors. This article focuses on a specific and by no means minor aspect of such process that has hardly been studied: the narratives and actions promoted by perpetrators of the ESMA. This research analyzes the public statements of corporal Raúl Vilariño at the beginning of the transition to democracy (1984), and those of captain Adolfo Scilingo, during a period of impunity (1995). These two moments show how the public word of these repressors affected the visibility of the site, the qualification of the crime and “crime scene”, and how they contributed to compose a social truth. This analysis helps to understand two core developments in the work of remembering: on the one hand, the contention about the legitimation of a point of view; on the other hand, the “emblematizing process” of the place. It is a slow construction process that ultimately developed from an initial concept of ESMA, not only as a particular “crime scene” of disappeared persons, but also as a metonymic and emblematic figure signifying all the clandestine centers of horror.Keywords: Perpetrators; dictartoship; sites of memory; statements.